-5y+9=6y+3

Simple and best practice solution for -5y+9=6y+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5y+9=6y+3 equation:


Simplifying
-5y + 9 = 6y + 3

Reorder the terms:
9 + -5y = 6y + 3

Reorder the terms:
9 + -5y = 3 + 6y

Solving
9 + -5y = 3 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
9 + -5y + -6y = 3 + 6y + -6y

Combine like terms: -5y + -6y = -11y
9 + -11y = 3 + 6y + -6y

Combine like terms: 6y + -6y = 0
9 + -11y = 3 + 0
9 + -11y = 3

Add '-9' to each side of the equation.
9 + -9 + -11y = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -11y = 3 + -9
-11y = 3 + -9

Combine like terms: 3 + -9 = -6
-11y = -6

Divide each side by '-11'.
y = 0.5454545455

Simplifying
y = 0.5454545455

See similar equations:

| 6z+18=6z+18 | | 5x=4(x+10) | | -1+5y=-37 | | 6y-3(y-2)+3= | | x+(x+30)+(-39+3*x)=717 | | 5(2-y)-y=4(3-2y) | | -4x+4x-10=-10 | | 4x(3x-30)=180 | | 33+10p=25+14p | | 9q-2=3q+2 | | 10-n/6=24 | | -(7xy-10)+2(4xy+4)= | | 20x-5(4x)=-15 | | 10/2=y | | 9+2/3b=14 | | 12x=10x+7 | | 4p+7=p-8 | | 3u=15/7 | | -4x-4(-0.5)=38 | | -15-5x=-3(x+1) | | 6-v/-2=25 | | 0.5(10x-5)=3 | | -3(4p+6)-2(5-11p)=3(2+3p) | | 4x^2+-x=0 | | -15-5x= | | 10+y/26=28 | | 8x^2+19x+3= | | -12=-2p+0.2(20-6p) | | 1/3(x+9)=8 | | 8=3y+6x | | 2y^2-2y^3-5y^2+5y^3= | | 9x^2-x+2=0 |

Equations solver categories